Mechanism on the promotion of host growth and enhancement of salt tolerance by Bacillaceae isolated from the rhizosphere of Reaumuria soongorica - Bao, Xinguang; Chong, Peifang; He, Cai; Wang, Xueying; Zhang, Feng (Frontiers in Microbiology, 2024)
Salt stress is a major abiotic stress that affects the growth of Reaumuria soongorica and many psammophytes in the desert areas of Northwest China. However, various Plant Growth-Promoting Rhizobacteria (PGPR) have been known to play an important role in promoting plant growth and alleviating the damaging effects of salt stress. In this study, three PGPR strains belonging to Bacillaceae were isolated from the rhizosphere of Reaumuria soongorica by morphological and molecular identification. All isolated strains exhibited capabilities of producing IAA, solubilizing phosphate, and fixing nitrogen, and were able to tolerate high levels of NaCl stress, up to 8-12%. The results of the pot-based experiment showed that salt (400 mM NaCl) stress inhibited Reaumuria soongorica seedlings' growth performance as well as biomass production, but after inoculation with strains P2, S37, and S40, the plant's height significantly increased by 26.87%, 17.59%, and 13.36%, respectively (p < 0.05), and both aboveground and root fresh weight significantly increased by more than 2 times compared to NaCl treatment.Additionally, inoculation with P2, S37, and S40 strains increased the content of photosynthetic pigments, proline, and soluble protein in Reaumuria soongorica seedlings under NaCl stress, while reducing the content of malondialdehyde and soluble sugars.Metabolomic analysis showed that strain S40 induces Reaumuria soongorica seedling leaves metabolome reprogramming to regulate cell metabolism, including plant hormone signal transduction and phenylalanine, tyrosine, and tryptophan biosynthesis pathways.Under NaCl stress, inoculation with strain S40 upregulated differential metabolites in plant hormone signal transduction pathways including plant hormones such as auxins (IAA), cytokinins, and jasmonic acid. The results indicate that inoculation with Bacillaceae can promote the growth of Reaumuria soongorica seedlings under NaCl stress and enhance salt tolerance by increasing the content of photosynthetic pigments, accumulating osmoregulatory substances, regulating plant hormone levels, and inducing phenylalanine metabolism. This study contributes to the enrichment of PGPR strains capable of promoting the growth of desert plants and has significant implications for the psammophytes growth and development in desert regions, as well as the effective utilization and transformation of saline-alkali lands.